Mesozoic Tectono-Thermal Event of the Qinshui Basin, Central North China Craton: Insights From Illite Crystallinity and Vitrinite Reflectance - Liu, Runchuan; Ren, Zhanli; Yang, Peng; He, Huaiyu; Smith, Thomas M.; Guo, Wei; Wu, Lin (Frontiers in Earth Science, 2021)
The Qinshui Basin is in the Central Orogenic Belt of the North China Craton (NCC), and the production of coalbed methane accounts for 70% of China's total coalbed methane output. Aiming at the basin’s unclear dynamic causes of large-scale coalbed methane accumulation and the unclear response relationship with the destruction of the NCC, we present joint illite crystallinity and vitrinite reflectance study across Zijin Shan and Qincan 1 well of Qinshui Basin, respectively. Inverse modeling suggested that tectono-thermal events occurred during the Early Cretaceous, associated with the maximum burial depth and heat flow. The maximum paleo-geothermal temperature and gradient reconstruction results recorded at the Carboniferous strata are 180~190°C and 6.5°C/100m. The denudation thicknesses recorded by illite crystallinity of Zijinshan and the vitrinite reflectance of Qincan 1 Well are 3180.63 m and 3269.32 m, respectively. We propose that the Qinshui Basin was affected by the extensional environment of NCC, which caused deep lithospheric thinning and magma upwelling, and a tectono-thermal event occurred during the Early Cretaceous in Qinshui Basin. In addition, the accumulation of coalbed methane, triggered by a tectono-thermal event during the Early Cretaceous, is consistent with the early Cretaceous accumulation and mineralization events in the NCC. Overall, our results reflect the subduction event influence of the western Pacific plate into the East Asian continental plate on the tectono-thermal history of the Central Orogenic Belt of NCC, which is theoretical significant for clarifying the thermal lithospheric thickness and rheological structure of the basin, as well as the evolutionary history of coalbed methane, and the basin response relationship to the destruction of the NCC.